Rose/House - Martine, Arkady (Tor Publishing Group, 2025)
Rose/House is a breathtaking and taut sci-fi gothic thriller from Arkady Martine, Hugo Award-winning author of A Memory Called Empire."I'm a piece of architecture, Detective. How should I know how humans are like to die?"All of Basit Deniau's houses were haunted. Rose House, his final architectural triumph built in the remote Mojave desert, was perhaps the most. A house embedded with an artificial intelligence is a common thing. But a house that is an artificial intelligence, infused in every crevice and corner with a thinking creature that is not human? That is something else altogether. That is Rose House. When Detective Maritza Smith gets a call from Rose House, she's shocked to learn that there is a dead body behind its sealed-up door. Everybody in town knows it's haunted. But Basit died more than a year ago, and everybody also knows that only his former protege, Dr. Selene Gisil, is permitted inside. But Selene wasn't in the country when Rose House called in the death. Who is the dead body? How did they get in? And who--or what--killed them? The answers lie within the labyrinthine halls of Rose House. But even if Martiza can get inside, there is no guarantee she will ever be able to leave ...